Coping During the COVID-19 Pandemic: A Qualitative Study of Older Adults Across the United States - Finlay, Jessica M.; Kler, Jasdeep S.; O'Shea, Brendan Q.; Eastman, Marisa R.; Vinson, Yamani R.; Kobayashi, Lindsay C. (Frontiers in Public Health, 2021)
Objective: Older adults may struggle with stresses and daily life challenges associated with the Coronavirus Disease 2019 (COVID-19) pandemic. Yet they may also utilize emotional and behavioral coping strategies. This qualitative paper aims to identify ways of coping with worries and stress during the pandemic from the perspectives of older adults in the United States. Methods: The COVID-19 Coping Study recruited 6,938 adults aged ≥55 through online multi-frame sampling from April 2-May 31, 2020 across all 50 US states, the District of Columbia, and Puerto Rico. The online questionnaire focused on the effects of COVID-19 on daily life, mental health, and well-being. This included an open-ended question regarding participants' coping strategies. We used qualitative content analysis to identify and code diverse coping strategies. Our general inductive approach enabled findings to emerge from the most frequent and dominant themes in the raw data. Results: A total of 5,180 adults [74% of the total sample; mean age 67.3 (SD 7.9); 63.8% female] responded to the question about using strategies to cope with living through the COVID-19 pandemic. Frequently-reported strategies included exercising and going outdoors, modifying routines, following public health guidelines, adjusting attitudes, and staying socially connected. Some coping strategies were health-limiting (e.g., overeating), while most strategies encouraged self-improvement, positive adjustment, and wellness. Conclusions: This study provides novel qualitative evidence on coping strategies of older adults early in the COVID-19 pandemic. Findings can inform community and clinical interventions to support older adults that harness positive coping strategies such as exercise, modified routines, and social strategies to improve physical and mental health, foster social support, and encourage meaningful daily activities during times of stress and trauma.